The Attitudes of Al-Quds Open University students towards e-learning - Jamal, Asmahan Mousa (Journal of Humanities & Social Sciences, 2022)
The study aimed to identify the trends of Al-Quds Open University students towards e-learning in the Hebron governorate, and the researcher used the descriptive analytical approach through applying a questionnaire consisting of (30) paragraphs after confirming their reliability and consistency, where the questionnaire was applied to a sample of (100) students Of Al-Quds Open University students in the Hebron Governorate who were registered for the academic year (2019-2020), were chosen randomly, and the study found that the trends of Al-Quds Open University students towards e-learning were large with an average arithmetic of (3.80), and the study also found that there were no differences Statistically significant In the directions of Al-Quds Open University students towards e-learning attributed to the variables (gender, number of electronic courses that you studied, academic level, specialization, the presence of a computer at home, the availability of a permanent Internet for you), and in light of these results the researcher came out with a set of recommendations. The most important results of the research were that the attitudes of Al-Quds Open University students towards e-learning were large, as the arithmetic mean of the total degree was (3.80) with a percentage of (76.0%), and the arithmetic averages ranged between (3.46- 4.32). And to the absence of statistically significant differences at the significance level (0.05 ≤) between the averages of Al-Quds Open University students’ attitudes towards e-learning due to the study variables: gender, number of electronic courses studied by the student, the student’s academic level, the presence of a computer at home, the student’s specialization and availability A permanent Internet network for the student, and in light of these results, the researcher came up with a set of recommendations, the most important of which is the need for Al-Quds Open University to continue adopting e-learning as an educational policy with its continuous development and investment of these positive trends for students towards e-learning and the development of plans and programs to benefit from these